1985
DOI: 10.1021/j100249a025
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture in cyanine dye aggregates at the air-water interface. Effect of monolayer composition and organization on fluorescent behavior

Abstract: The fluorescence behavior of an amphiphatic oxacyanine dye and its thiacyanine analogue has been investigated in spread monolayers at the air-water interface. J-aggregate formation as a function of area/(dye molecule) was monitored by spectral changes in pure dye monolayers and in 1:1 mixtures of dye with various fatty acid coaggregates. Simultaneously, the thermodynamic behavior of these systems was characterized by the associated surface pressure-area isotherms. In all cases, J-aggregate formation may be rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 3 publications
0
25
0
1
Order By: Relevance
“…of the constituents occurs. 13,21,22 The concentration for half-quenching (4.55 ± 0.1 1012 molecules/cm2) is not dramatically different from that reported by Costa et al (4.3 X 1012 molecules/cm2) in transferred phytol monolayers as well as that given by Tweet et al in oleoyl alcohol mentioned above.3,5 (Applying eq 1 to their data gives C0 ~4.0 X 1012 molecules/cm1 2.) The fit of both kinds of Chi a data to a close second-order dependence on concentration over the range of these measurements indicates the dominance of trapping involving statistical pairs of molecules, as has long been suggested.19 However, the agreement in C0 between the two types of measurements suggests the dominance of a dynamic process, either by diffusion of the excited molecule to a trap or migration of the exciton among molecules in the array.…”
Section: Discussionmentioning
confidence: 68%
“…of the constituents occurs. 13,21,22 The concentration for half-quenching (4.55 ± 0.1 1012 molecules/cm2) is not dramatically different from that reported by Costa et al (4.3 X 1012 molecules/cm2) in transferred phytol monolayers as well as that given by Tweet et al in oleoyl alcohol mentioned above.3,5 (Applying eq 1 to their data gives C0 ~4.0 X 1012 molecules/cm1 2.) The fit of both kinds of Chi a data to a close second-order dependence on concentration over the range of these measurements indicates the dominance of trapping involving statistical pairs of molecules, as has long been suggested.19 However, the agreement in C0 between the two types of measurements suggests the dominance of a dynamic process, either by diffusion of the excited molecule to a trap or migration of the exciton among molecules in the array.…”
Section: Discussionmentioning
confidence: 68%
“…It is interesting to mention in this context that S. Vaidyanathan et al [47] reported the enhancement of contact and aggregate formation of cationic cyanine dyes by mixing oppositely charged coaggregate. Where oppositely charged coaggregate decreases the charge repulsion between the dye chromophore.…”
Section: Dilution Experiments Of Nk J-aggregates In Otabmentioning
confidence: 99%
“…2.5 nm. 20 This energy-transfer reaction together with the broad and infrared-shied absorption spectrum of the OTCC aggregates prove that these lms might be integrated in molecular electronic devices, as light emitting diodes or solar cells.…”
Section: Energy Transfer From An Ir Complex To Otcc On Quartzmentioning
confidence: 94%